Batch biosorption studies of ammonical nitrogen (NH3-N) ions from aqueous solutions using the ubiquitous bacteria Klebsiella sp.: equilibrium, kinetic, and thermodynamic studies - Fadaa Alown; Fuad Ameen; Ashiwin Vadiveloo (Annals of Microbiology)
Abstract Background The ubiquity of ammonical nitrogen (NH3-N) in aquatic habitats is a contradictory phenomenon since it serves a crucial function in maintaining these ecosystems, yet when levels are too high, they can have adverse effects on ecological balance and human welfare. An extensive set of batch tests were used in this study to see how well the bacterial species Klebsiella sp. broke down ammonical nitrogen (NH3-N). Results The research results established that Klebsiella sp. has a remarkable capacity to adapt to ammonical nitrogen concentrations of up to 125 mg/l over a long period of time. The adaptation process depends on several factors such as biomass abundance, ammonical nitrogen concentration, pH, and temperature. This study identified the optimal method for the absorption of ammonical nitrogen (NH3-N) from a solution at a concentration of 100 parts per million (ppm), achieving an efficiency of 89 ± 1.5% mg/g under specified conditions. At a pH of 6.5, the adsorbent dosage was 0.3 g in 50 milliliters of NH3-N at a temperature of 26 degrees C. We used an extensive range of analytical techniques, such as Scanning Electron Microscopy, Xray diffraction, Brunauer-Emmett-Teller analysis, Transmission Electron Microscopy, and Fourier-Transform Infrared Spectroscopy, to confirm the accuracy of our results. The study also showed that the biosorption process closely followed pseudo-second-order kinetics and the Langmuir model, which propose that both physical and chemical processes were involved. The thermodynamic studies also showed that this process can happen on its own and can be used in industry. Conclusion This study emphasizes the great ability of Klebsiella sp. to reduce NH3-N, providing important knowledge for water quality management and aquatic ecosystem preservation. Graphical Abstract